PERBEDAAN PENAMBAHAN BAHAN PENUNJANG COOKIES PADA METODE CREAMING TERHADAP PENERIMAAN SENSORIK COOKIES TEPUNG KOMPOSIT JAGUNG PUTIH LOKAL TIMOR DAN DAUN KELOR (Moringa oleifera) - Maria Susana Medho; Endeyani V. Muhammad; Maria Klara Salli (Politeknik Pertanian Negeri Kupang, 2022)
This study aims to evaluate the effect of different supporting ingredients on the creaming method in making cookies on the panelists sensory acceptance. The different variations of material, that P1 = all ingredients with VCO as a substitute for butter, and without egg; P2 = all ingredients with eggs and VCO ; P3 = all ingredients with butter and eggs; P4 = all ingredients with butter and without eggs. Parameters of sensory reception that the level of preference for color, texture, taste, smell. The results showed that the highest value was in P1 and P4 with a preference for color 4.00 and 3.59, texture 4.12 and 4.18, taste 4.47 and 3.59, smell 3.94 and 3.47. Treatment of P4 has fulfilled of the standard physical test criteria of cookies, that is specific smell of cookies, sweet taste, specific color based on the added coloring agent, crunchy texture and not easy to crumble.Key Words: Acceptance, sensory, cookies, composit flour